2000
DOI: 10.1021/bi000779p
|View full text |Cite
|
Sign up to set email alerts
|

N-Glycosylation and Residue 96 Are Involved in the Functional Properties of UDP-Glucuronosyltransferase Enzymes,

Abstract: The recent cloning of several human and monkey UDP-glucuronosyltransferase (UGT) 2B proteins has allowed the characterization of these steroid metabolic enzymes. However, relatively little is known about the structure-function relationship, and the potential post-translational modifications of these proteins. The mammalian UGT2B proteins contain at least one consensus asparagine-linked glycosylation site NX(S/T). Endoglycosidase H digestion of the human and monkey UGT2B proteins demonstrates that only UGT2B7, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
37
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 45 publications
7
37
0
Order By: Relevance
“…Thus, it is conceivable that human UGT1As are commonly N-glycosylated at the sites corresponding to N292 and N344 of UGT1A9, which are encoded from common exons 2 and 5, although the extent of glycosylation and/or size of the glycan are different. The mutation of these asparagine residues significantly decreased the Vmax values, but not the Km values (Table 2), consistent with a previous study of human UGT2B15 and monkey UGT2B20 [8]. To investigate whether the decreased velocity was due to the abolished glycosylation, not by the change in primary structure, we further studied the enzyme activity of unglycosylated and deglycosylated UGT1A9 proteins.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Thus, it is conceivable that human UGT1As are commonly N-glycosylated at the sites corresponding to N292 and N344 of UGT1A9, which are encoded from common exons 2 and 5, although the extent of glycosylation and/or size of the glycan are different. The mutation of these asparagine residues significantly decreased the Vmax values, but not the Km values (Table 2), consistent with a previous study of human UGT2B15 and monkey UGT2B20 [8]. To investigate whether the decreased velocity was due to the abolished glycosylation, not by the change in primary structure, we further studied the enzyme activity of unglycosylated and deglycosylated UGT1A9 proteins.…”
Section: Discussionsupporting
confidence: 88%
“…However, it should be pointed out that some UGT2B isoforms are not glycosylated. Barbier et al [8] reported that human UGT2B4, monkey UGT2B18 and UGT2B23 are not N-glycosylated in spite of the presence of the potential N-glycosylation sites. Additionally, there is no potential N-glycosylation site for rat UGT2B3 [9] and UGT2B6 [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such higher activities in the HEK293 system than the Supersomes were also observed for the glucuronidations of 5-(4Ј-hydroxyphenyl)-5-phenylhydantoin (Nakajima et al, 2007) and N-hydroxy-2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine (Malfatti and Felton, 2004;Dellinger et al, 2007). The differences in the membrane environment or lipid components and/or the differences in the post-translational modulation of UGT such as glycosylation or phosphorylation between the host cells (Barbier et al, 2000;Basu et al, 2005) may be involved in the inconsistency. In the present study using Supersomes, the V max values of UGT1A8 and UGT1A10 were considerably lower than those of UGT1A7 and UGT1A9 for 4-MU and p-NP O-glucuronidations.…”
Section: Discussionmentioning
confidence: 97%
“…This discrepancy may be explained by the fact that the relationship between amount of mRNA and "signal" in the branched chain assay (method used by Shelby et al, 2003) is not necessarily constant, due to the sequences of the oligonucleotide probes and their specific characteristics. Alternatively, these inconsistencies may be explained by post-translational changes in UGT activity resulting from phosphorylation or glycosylation or by inconsistent relationships between mRNA and protein expression when different proteins are compared (Barbier et al, 2000;Basu et al, 2003).…”
Section: Discussionmentioning
confidence: 99%